Pelatihan Penggunaan KIT Media Pembelajaran Matematika di SDN 4 Bebidas - Radiusman Radiusman; Lalu Sirajul Hadi; Heri Setiawan; Irwandi Putra Ramli; Lalu Rafta Patech; Catur Prima Putra Abdullah; Jundu Muhammad Mufakkirul Islami; Heri Hadi Saputra; Ade Andriyan; Syarifudin Syarifudin (Educational Consultant & Counseling Career (EC3) Mataram, 2026)
The use of mathematics learning media kits is still rarely used in learning activities. The lack of training experienced by teachers on how to use them prevents them from utilizing the available facilities. This lack of use of mathematics learning media kits also results in less enjoyable mathematics learning in the classroom and less than satisfactory results. The purpose of this community service activity was to conduct training on the use of mathematics learning media kits at SDN 4 Bebidas. The methods used in this community service activity included material delivery, question and answer sessions, training, and hands-on practice using the mathematics learning media kits. This community service activity consisted of several stages: socialization, preparation, implementation, and reflection. Based on the community service activities, teachers at partner schools observed that the use of media made students more active and communicative, resulting in better results. Teachers at partner schools also felt that this Community Service Program (PKM) indirectly strengthened collaboration and communication among teachers to improve the quality of mathematics learning.